THE INFLUENCE OF MARGIN MURABAHA RECOGNITION METHOTD ON ISLAMIC BANKING SUSTAINABILITY - Fithrah Kamaliyah (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
The purpose of this study was to analyze the two method of margin murabaha recognition in Indonesian Islamic banking, they are proportional and annuity. How they effect business sustainability expressed by level of risks and the soundness of Islamic banks. The object of research is Bank Muamalat Indonesia according to its Annual Financial Statements in period 2001-2014. This research using SEM analysis to see the influence of both methods. The result of this study, suggesting that proportional method has 45% influence on the level of risk and 23% of the bank’s soundness. The annuity method has 51% on the level of risk and 57% of the bank’s soundness negatively